Prepoznavanje socialnih veščin pri glasbenih dejavnostih v skupini tri- in štiriletnih otrok v vrtcu - Zadnik, Katarina; Smrekar, Sara (Revija za elementarno izobraževanje, 2020)
Recognition of social skills during music activity among three- and four-year-old children in kindergarten. The positive effects of music activities on social development have been substantiated as secondary results in Slovenian research studies. In the contribution, we used a sample of ten 3- and 4-year-olds to study the development of social skills during music activities in kindergarten. The research findings showed that the frequency of involvement and participation in music activities, instrument sharing, establishing contacts and mutual cooperation gradually increased over the six-month period. The resultsshowed that music activities also prompted a higher frequency of sharing toys, various objects, as well as greater mutual cooperation and engagement among children in other kindergarten activities.
Keywords: preschool children, musical activities, social skills, establishing contacts, sharing musical instruments